Artistic Education and Psychomotor Development in Primary (Journal of Parents and Teachers, 2014)
Through experiences and activities of Artistic Education and Psychomotricity, students get to know better the environment around them and they get a more functional learning. It provides pleasure and a playful component that drives children to want to learn. The article explains some examples of how to do this task.
Keywords: Artistic; Psychomotricity; interdisciplinarity; playful learning; meaningful learning